1995
DOI: 10.1161/01.str.26.11.2061
|View full text |Cite
|
Sign up to set email alerts
|

Potential and Limitations of Transcranial Color-Coded Sonography in Stroke Patients

Abstract: TCCS is a noninvasive bedside method that provides rapid and reliable data regarding stroke subtype and mechanism immediately after onset. Window failure is a serious limitation of this method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
115
1
4

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(125 citation statements)
references
References 14 publications
5
115
1
4
Order By: Relevance
“…The percentage of patients requiring UCA enhancement in the present study is markedly lower compared with a previous report 14 that analyzed the number of acute stroke patients in whom UCA was necessary for TCCD examination (8.8% versus 20%, respectively). Several reasons may have contributed to this discrepancy.…”
Section: Discussioncontrasting
confidence: 84%
“…The percentage of patients requiring UCA enhancement in the present study is markedly lower compared with a previous report 14 that analyzed the number of acute stroke patients in whom UCA was necessary for TCCD examination (8.8% versus 20%, respectively). Several reasons may have contributed to this discrepancy.…”
Section: Discussioncontrasting
confidence: 84%
“…43,44 Nevertheless, the use of sonographic contrast agents has been shown to increase significantly the number of valid sonographic investigations and should be kept in mind as an additional option in these patients. 45 Sonographic contrast agents improve detection of maximum flow velocities, which has to be kept in mind when applying our established data.…”
Section: Discussionmentioning
confidence: 99%
“…According to conventional ce-TCDS studies, failure to perform the transcranial examination has been reported in up to 40% of cases. 14,15 The problem of an insufficient acoustic bone window for the ce-TCDS detection of RLS can be virtually solved by performing extracranial carotid duplex sonography. We made use of pulse inversion-based contrast-enhanced harmonic imaging, which enables the visualization of single UCA microbubbles in the vessel lumen because of their nonlinear backscatter.…”
Section: Discussionmentioning
confidence: 99%